Unusual Cause of Bilateral Posterior Shoulder Fracture Dislocation: A Case Report - Owayed Ali Al-Mutairi; Awdhah Abdulkarim; Khaled Wahdan; Yahia Al-Shammari (Case Reports in Orthopedic Research, 2021)
A 34-year-old man presented 2 weeks after sustaining posterior fracture dislocation of both shoulders due to a fall from a bicycle while riding downhill. Posterior fracture dislocation of both shoulders is typically caused due to seizures or electrocution. In our patient, the injury was caused by trauma, which is exceedingly rare. Owing to the late presentation, management of such injuries usually entails joint replacement; however, due to his young age, both shoulders were treated with open reduction and internal fixation. Bilateral posterior shoulder fracture dislocation is rarely encountered in clinical practice.